VD_FINDINFO HC / 2016 / 712 vom 11. Juli 2016 - VD Tribunal cantonal (2016)
SUSPENSION DE LA PROCÉDURE, UNITÉ DU JUGEMENT DE DIVORCE | 165 al. 2 CC, 126 CPC (CH), 283 CPC (CH), 319 let. b ch. 1 CPC (CH)